Sulzer centrifugal pump handbook (Butterworth-Heinemann, 2010)
This long-awaited new edition is the complete reference for engineers and designers working on pump design and development or using centrifugal pumps in the field. This authoritative guide has been developed with access to the technical expertise of the leading centrifugal pump developer, Sulzer Pumps. In addition to providing the most comprehensive centrifugal pump theory and design reference with detailed material on cavitation, erosion, selection of materials, rotor vibration behavior and forces acting on pumps, the handbook also covers key pumping applications topics and operational issues, including operating performance in various types of circuitry, drives and acceptance testing. Enables readers to understand, specify and utilise centrifugal pumps more effectively, drawing on the industry-leading experience of Sulzer Pumps, one of the world's major centrifugal pump developers. Covers theory, design and operation, with an emphasis on providing first class quality and efficiency solutions for high capital outlay pump plant users. Updated to cover the latest design and technology developments, including applications, test and reliability procedures, cavitation, erosion, selection of materials, rotor vibration behaviour and operating performance in various types of circuitry.
Previous ed.: Kidlington: Elsevier Advanced Technology, 1998.
Keywords: Centrifugal pumps -- Handbooks, manuals, etc.; elektronické knihy; electronic books